Копінг-поведінка майбутніх правоохоронців у контексті прогностичної компетентності - Швець, Д. В.; Shvets, D. V.; ORCID: http://orcid.org/0000-0002-1999-9956; ResearcherID: B-9071-2018 (Актуальные проблемы психологии: сб. науч. тр. ин-та писхологии им. Г. С. Костюка НАПН Украины. – 2017. – Т. 6. – Вып. 13 – С. 188-197, 2017)
У сучасному світі професійна діяльність співробітників правоохоронних органів протікає в екстремальних умовах і зазнає впливу різних стрес-факторів. Проблема психологічної адаптації працівників органів внутрішніх справ до стресу одне з провідних положень, оскільки від ефективності її розв’язання безпосередньо залежить ефективність діяльності правоохоронців. В цілому курсантам з високим рівнем антиципаційної спроможності властиво використовувати конструктивні стратегії подолання стресових ситуацій (соціальний контакт, проблемний аналіз), а курсантам з низьким рівнем антиципаційної неспроможності – неконструктивні копінг-стратегії (непрямі, асоціальні дії, самозвинувачення).

Nowadays, the professional law enforcement activities take place in extreme conditions and expose to various stress factors. Choosing the right strategies to overcome traumatic events is impossible without the cognitive evaluation of the problem situation that allows prediction of the possible result. The data indicate that students with high levels of anticipation viability inherent in such adaptive strategies: active (assertive action) and prosocial (social contact), which are aimed at solving the problem situation or receiving social support from the environment. And students with low predictive competence inherent maladaptive coping strategy: indirect (manipulative actions) and asocial, which are characterized by social diffidence. Regarding the specifics of coping mechanisms the following results were obtained: the cadets with a high level of anticipation viability in a stress situation most often use productive coping strategies in cognitive ("problem analysis", "preservation of aplomb" and "installing selfworth"), emotional ("optimistic", "protest") and behavioral ("altruism", "cooperation"). In turn, students with low anticipation viability in a stressful situation, use maladaptive coping strategies in cognitive ("ignoring", "dissimilation") and emotional ("suppression of emotions", "self-blame") areas. In the behavioral realm they tend to use relatively productive coping mechanisms ("compensation", "constructive activity", "prevention"). In general coping strategies can help or hinder the success of overcoming stress, but also affect the health preservation of the subject.

В современном мире профессиональная деятельность сотрудников правоохранительных органов протекает в экстремальных условиях и подвергается воздействию различных стресс-факторов. Проблема психологической адаптации сотрудников органов внутренних дел к стрессу одно из ведущих положений, поскольку от эффективности ее решения напрямую зависит эффективность деятельности правоохранительных органов. В целом курсантам с высоким уровнем антиципационной состоятельности свойственно использовать конструктивные стратегии преодоления стрессовых ситуаций (социальный контакт, проблемный анализ), а курсантам с низким уровнем антиципационной состоятельности – неконструктивные копинг-стратегии (косвенные, асоциальные действия, самообвинения).
Coping behavior of future law enforcement officers in the context of predictive competence
Копинг-поведение будущих правоохранителей в контексте прогностической компетентности
Швець, Д. В. Копінг-поведінка майбутніх правоохоронців у контексті прогностичної компетентності / Д. В. Швець // Актуальные проблемы психологии: сб. науч. тр. ин-та писхологии им. Г. С. Костюка НАПН Украины. – 2017. – Т. 6. – Вып. 13 – С. 188-197.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Україна. Ukraine. Украина; копінг-поведінка; стрес; компетенція; прогностична компетентність; антиципаційна спроможність; правоохоронці; поліція; полиция; police; правоохранители; копинг-поведение; стресс; компетенция; прогностическая компетенция; антиципационная состоятельность; coping behavior; stress; competence; anticipation viability; law enforcement officers